T1ρ, T2 mapping, and EPIC‐µCT Imaging in a Canine Model of Knee Osteochondral Injury. Issue 2 (3rd September 2019) - Franklin, Samuel P.; Stoker, Aaron M.; Lin, Angela S. P.; Pownder, Sarah L.; Burke, Emily E.; Bozynski, Chantelle C.; Kuroki, Kei; Guldberg, Robert E.; Cook, James L.; Holmes, Shannon P.
ABSTRACT: The dog is the most commonly used large animal model for the study of osteoarthritis. Optimizing methods for assessing cartilage health would prove useful in reducing the number of dogs needed for a valid study of osteoarthritis and cartilage repair. Twelve beagles had critical‐sized osteochondral defects created in the medial femoral condyle of both knees. Eight dogs had T1ρ and T2 magnetic resonance imaging (MRI) performed approximately 6 months after defect creation. Following MRI evaluations, all 12 dogs were humanely euthanatized and cartilage samples were obtained from the medial and lateral femoral condyles, medial and lateral tibial plateaus, trochlear groove, and patella for proteoglycan and collagen quantification. Equilibrium partitioning of an ionic contrast (EPIC)‐µCT was then performed followed by the histologic assessment of the knees. Correlations between T1ρ, T2, EPIC‐µCT and proteoglycan, collagen, and histology scores were assessed using a multivariate analysis accounting for correlations from samples within the same knee and in the same dog. Pearson's correlation coefficients were calculated to assess the strength of significant relationships. Correlations between µCT values and biochemical or histologic assessment were weak to moderately strong (0.09–0.41; p < 0.0001–0.66). There was a weak correlation between the T2 values and cartilage proteoglycan (−0.32; p = 0.04). The correlation between T1ρ values and cartilage proteoglycan were moderately strong (−0.38; p < 0.05) while the strongest correlation was between the T1ρ values and histological assessment of cartilage with a correlation coefficient of 0.58 ( p < 0.0001). These data suggest that T1ρ shows promise for possible utility in the translational study of cartilage health and warrants further development in this species. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:368‐377, 2020